PEMBELAJARAN SEJARAH LOKAL PADA SEKOLAH MENENGAH ATAS (STUDI KASUS DI SMA N 1 DAN SMA N 8 PONTIANAK) - Andang Firmansyah (Universitas Negeri Malang, 2021)
History learning should prioritize local wisdom values that grow in their respective communities. This is, so that future generations do not lose their identity and pride in their region. In learning local history, the next generation must know and understand what happened in the past in their society. This causes future generations to learn from their predecessors and be able to take local wisdom values. Therefore, local history material in history learning in senior high schools is vital. This study aimed to determine the use of local historical sources, teacher preparation in learning, the delivery process, and students' understanding of history learning. The form of this research is qualitative with a research strategy using case studies. The results showed that SMA N 1 Pontianak was better at utilizing local historical sources. This is because the quality of teachers and supporting facilities are of high quality. The SMA N 1 learning implementation plan at the design stage has also included local history materials. Then the delivery process in both schools shows that the teachers are good enough and creative and adjust to each school's conditions. Then the understanding of students in both schools to learn local history is good enough. This is due to students' interest in these materials.